2018
DOI: 10.1007/s12975-018-0647-6
|View full text |Cite
|
Sign up to set email alerts
|

Large Vessel Vasospasm Is Not Associated with Cerebral Cortical Hypoperfusion in a Murine Model of Subarachnoid Hemorrhage

Abstract: Clinical studies on subarachnoid hemorrhage (SAH) have shown discrepancies between large vessel vasospasm, cerebral perfusion, and clinical outcome. We set out to analyze the contribution of large vessel vasospasm to impaired cerebral perfusion and neurological impairment in a murine model of SAH. SAH was induced in C57BL/6 mice by endovascular filament perforation. Vasospasm was analyzed with microcomputed tomography, cortical perfusion by laser SPECKLE contrast imaging, and functional impairment with a quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
(80 reference statements)
2
12
0
Order By: Relevance
“…We also observed cerebral hypoperfusion in the absence of severe vasospasm in some cases. These observations were consistent with previous studies, which showed that vasospasm and cerebral hypoperfusion can occur independently (30,33,34) and that DCI has a multifactorial genesis (4). Again, this highlights the need for multimodal monitoring of SAH patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also observed cerebral hypoperfusion in the absence of severe vasospasm in some cases. These observations were consistent with previous studies, which showed that vasospasm and cerebral hypoperfusion can occur independently (30,33,34) and that DCI has a multifactorial genesis (4). Again, this highlights the need for multimodal monitoring of SAH patients.…”
Section: Discussionsupporting
confidence: 92%
“…In brief, the bone was virtually subtracted and the intracranial vascular tree was then virtually reconstructed by applying a standardized windowing procedure (23,24) shown to have high interrater agreement in results for vessel volumes (24). The vessel volume and the length of the corresponding vessel segment were calculated according to a standardized algorithm, as previously described (23,24,29,30), for the following vessel segments: the basilar artery, the posterior cerebral artery, the internal carotid artery, the M1 and M2 segments of the middle cerebral artery, and the A1 and A2 segments of the anterior cerebral artery. To account for individual differences in the length of the vessel segments, the vessel volumes were expressed in relation to the vessel length (volume/length ratio).…”
Section: Volumetric Analysis Of Cta Datamentioning
confidence: 99%
“…Subarachnoid haemorrhage was induced by endovascular filament perforation under isoflurane anaesthesia (Abbvie, Wiesbaden, Germany) with continuous ICP monitoring as described previously 28–30 . Anaesthesia was induced with 4% isoflurane for 1 min and maintained with 2% isoflurane and 40% O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Delayed cerebral ischemia may be caused by cerebral vasospasm, cortical spreading depolarization, and microcirculatory dysfunction [12], which may occur secondary to EBI [13]. Although cerebral vasospasm remains an important cause of delayed cerebral ischemia [14], microcirculatory disturbance and cortical spreading depolarization may be more important than cerebral vasospasm as to the impact on functional outcomes especially in poor-grade SAH patients [15]. Thus, many basic researchers have worked hard to overcome EBI, which is believed eventually to improve outcomes of poor-grade SAH patients.…”
mentioning
confidence: 99%